Spectroscopic characterization, photoinduced processes and cytotoxic properties of substituted N‐ethyl selenadiazoloquinolones†. (20th May 2013) - Barbieriková, Zuzana; Bella, Maroš; Sekeráková, Ľudmila; Lietava, Jozef; Bobeničová, Miroslava; Dvoranová, Dana; Milata, Viktor; Sádecká, Jana; Topoľská, Dominika; Heizer, Tomáš; Hudec, Roman; Czímerová, Adriana; et al.
Abstract : 7‐R‐9‐ethyl‐6, 9‐dihydro‐6‐oxo‐[1, 2, 5]selenadiazolo[3, 4‐ h ]quinolines (R = H, COOC2 H5, COOCH3, COOH and COCH3, E1h, E2h, E3h, E4h, E5h ) and 6‐ethyl‐6, 9‐dihydro‐9‐oxo‐[1, 2, 5]selenadiazolo[3, 4‐ f ]quinoline (E1f ) were characterized by UV/vis, FT‐IR and fluorescence spectroscopy. The electronic absorption spectra of the derivativesE1h, E2h, E3h andE5h in the aprotic solvents dimethylsulfoxide (DMSO) and acetonitrile (ACN) reveal low‐energy absorption maxima with λ max > 400 > nm, shifted hypsochromically in water. In DMSO, N ‐ethyl selenadiazoloquinolones behave as strong fluorescent agents ( λ em ≥ 550 nm) with the exception of the carboxylic acid derivativeE4h which shows only poor emission. Photoinduced reactions of N ‐ethyl selenadiazoloquinolones were investigated by means of electron paramagnetic resonance (EPR) spectroscopy. Photoexcitation of N ‐ethyl selenadiazoloquinolones in aerated DMSO with either 385 nm or 400 nm wavelengths, monitored by EPR spin trapping technique, results in the generation of superoxide radical anions; under an inert atmosphere, the generation of methyl radicals originating from the solvent predominates. Upon exposure at either 365 nm, 385 nm or 400 nm, aerated ACN solutions of selenadiazoloquinolones in the presence of sterically hindered amines produce nitroxide radicals via a reaction with photogenerated singlet oxygen. The 7‐substituted derivatives of 9‐ethyl‐6, 9‐dihydro‐6‐oxo‐[1, 2, 5]selenadiazolo[3, 4‐ h ]quinoline behave as photosensitizers activating molecular oxygen upon photoexcitation and possess the sufficientphotochemical stability under the given experimental conditions. The cytotoxic effects of non‐photoactivated and UVA photoactivated N ‐ethyl substituted selenadiazoloquinolones on cancer (human HeLa and murine L1210) and non‐cancer (NIH‐3T3) cell lines were monitored by the MTT test. The derivativeE2h demonstrates the highest cytotoxic/photocytotoxic activity on the neoplastic cell lines. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : 7‐R‐9‐ethyl‐6, 9‐dihydro‐6‐oxo‐[1, 2, 5]selenadiazolo[3, 4‐ h ]quinolines and 6‐ethyl‐6, 9‐dihydro‐9‐oxo‐[1, 2, 5]selenadiazolo[3, 4‐ f ]quinoline were synthesized and characterized by UV/vis, FT‐IR and fluorescence spectroscopy; the generation of superoxide radical anions and singlet oxygen was monitored by electron paramagnetic resonance spin trapping technique and sterically hindered amine oxidation.